The Impact of The Implementation of The MURDER Learning Strategy (Mood, Understanding, Recall, Digest, Expand, and riview) on Learning Outcomes in Islamic Education for Class VII Students at Muhammadiyah High School 33 Tomange, Jakarta School Year 2020/20 - Muhammad Mukhlas; Yuwana Alifratus Sholihah (Educan : Jurnal Pendidikan Islam, 2021)
Education is one form of human cultural realization that is dynamic and full of development. Therefore, the change or development of education is something that should happen in line with the changing culture of life. Changes in the sense of improving education at all levels need to be continuously made in anticipation of future interests. The realization of learning outcomes will always be related to evaluation activities. Therefore, learning evaluation techniques and procedures are required that can effectively assess the learning process and results. This study uses a quantitative approach of True Experimental type by using posttest only control design type. The subjects in this study were grade 7-2 as an experimental class and grade 7-3 as a control class at SMP Muhammadiyah 33 Tomang, Jakarta. The instrument used in this study is a test for data analysis. In this study to find out the results of data analysis using SPSS 24. From the results of the data analysis the average score of students in the experimental class was 76.83 while the average score in the control class was 73.63. Judging by Mann Whitney's testing of sig results. (2-tailed) of 0.321 which is 0.321 > 0.05, it can be concluded that there is no difference or influence on student learning outcomes in experimental classes and control classes Because during the research was conducted online due to this pandemic period. Based on the results of research that has been conducted to improve student learning outcomes in pai grade 7 subjects at SMP Muhammadiyah 33 Tomang Jakarta, researchers are further to further develop and improve the learning strategies used, and teachers should better supervise and pay attention to their students in order to concentrate more in the teaching and learning process so that the learning process is more effective and efficient and can hone cognitive aspects , affective and psychomotor.